Adoption and testing of the Gold Standard Smallholder Dairy Methodology - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The methodology has been tested by the implementation of the baseline survey. Lessons learned, and the data itself, will be used to inform and guide the development of Kenya’s Tier 2 GHG inventory for dairy cattle.